2017
DOI: 10.1038/ncomms15306
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective covalent organic functionalization of epitaxial graphene

Abstract: Graphene functionalization with organics is expected to be an important step for the development of graphene-based materials with tailored electronic properties. However, its high chemical inertness makes difficult a controlled and selective covalent functionalization, and most of the works performed up to the date report electrostatic molecular adsorption or unruly functionalization. We show hereafter a mechanism for promoting highly specific covalent bonding of any amino-terminated molecule and a description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 57 publications
(103 reference statements)
2
52
0
Order By: Relevance
“…This finding demonstrates that high quality grafting can be achieved in a set-up with growth conditions less demanding with respect to UHV-related methods 36 , therefore disclosing the possibility to apply photoemission techniques to systems prepared on the basis of similar electrochemical methods 37 , and ultimately enabling a scalable pathway for the production of functionalized graphene layers.…”
Section: Discussionmentioning
confidence: 82%
“…This finding demonstrates that high quality grafting can be achieved in a set-up with growth conditions less demanding with respect to UHV-related methods 36 , therefore disclosing the possibility to apply photoemission techniques to systems prepared on the basis of similar electrochemical methods 37 , and ultimately enabling a scalable pathway for the production of functionalized graphene layers.…”
Section: Discussionmentioning
confidence: 82%
“…FG was reacted with hydroxylamine (NH 2 OH) at 130 °C in dimethylformamide (DMF), avoiding high‐temperature treatment or highly reactive reagents, used previously . The Supporting Information presents a detailed characterization of pNG and the mechanism of its formation, which involves: i) the defluorination of FG and its transformation into highly N‐doped (9.8 at.%) graphene (see Figure S4A–D in the Supporting Information); ii) the decomposition of hydroxylamine into ammonia, (identified by trapping the byproducts of the reaction, as described in Figure S4E in the Supporting Information), which undergoes dehydrogenation at vacancies and is thus a source of the atomic nitrogen that becomes doped into the graphene lattice; iii) the in situ formation of lattice vacancies in FG (see Figure S5A,B in the Supporting Information); and iv) the formation of a predominantly sp 2 architecture (Figure S5C,D, Supporting Information). Atomic force microscopy (AFM) and transmission electron microscopy (TEM) indicated that pNG consisted mainly of nanosized flakes ( Figure A; Figure S6, Supporting Information).…”
mentioning
confidence: 99%
“…Organic covalent functionalization reactions of graphene include two general routes: (a) the formation of covalent bonds between free radicals or dienophiles and C═C bonds of pristine graphene and (b) the formation of covalent bonds between organic functional groups and the oxygen groups of GO (Georgakilas et al, 2012). Characteristic of these processes are the presence of carbonyl, hydroxyl and carboxyl groups (resulting from the oxidation of graphite itself by the Hummers method); nevertheless, functional moieties, such as amines (Wanjeri et al, 2018;Bueno et al, 2017), amides (Ahmed and Kim, 2017;Mrlík et al, 2016), nitro (Begum et al, 2017), thio-compounds (Mahmoodi et al, 2017;Cai and Larese-Casanova, 2016), carbene cycloaddition (Zan, 2014), among others, can be chemically added to the carbon plane edges and surface. Within the covalent routes, a functionalizing group, such as thionyl, can replace the hydroxyl groups that form on the graphene surface after oxidation (Cai and Larese-Casanova, 2016).…”
Section: Functionalization Of Graphene and Its Derivativesmentioning
confidence: 99%
“…The functionalization of graphene or graphene oxide (GO) nanosheets confers specific properties to the composites, e.g., their chemical selectiveness, solubility, thermal and electronic conductivity (Bueno et al, 2017;Xiang et al, 2016). Such enhancement allows the employment of functionalized graphenebased materials in several fields, such as chemistry and catalysis (Ye et al, 2018;Rana and Jonnalagadda, 2017), biomedicine (Kenry et al, 2018;Yu et al, 2018;Zeng et al, 2017), electronics (Scidà et al, 2018;Gevaerd et al, 2018;Chiu et al, 2017;Zhao et al, 2017), energy (Li and Zhi, 2018;Sadri et al, 2017) and environmental sciences and technologies (Ren et al, 2018;Othman et al, 2018;Khurana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation